The Fiction of Respect Individual Autonomy as a Kind Of Clínical Research Human Subject Explotation - Santos, Natalia Petersen Nascimento (2015)
This article promotes a discussion of western legal concept which sees individuals as subjects of rights, discussing the advisability of such a formulation in the context of clinical trials in humans, since the commonly borderline situation of vulnerability in which they are volunteers who submit to such procedures. For this purpose, it was used as a theoretical framework to work "Critical Introduction to Law" Michel Mialle, in which the author states in a forceful way that the construction of the legal institute of the "subject of law" and the imposition of unrestricted recognition of individual autonomy constitute a construction of the bourgeois state to facilitate the domination of vulnerable, so that this, although not legally obliged to practice certain behaviors, see forced by circumstances to act in line with the interests of that institution. It is argued, therefore, that autonomy to consent to participation in scientific trials must be assessed in each case, with special attention to circumstances which might vulnerabilizar voluntary research and mitigate their individual autonomy in the face of the experiments, under penalty to be subjecting the individual to harmful procedures to their lives and health for the benefit of capital society's interests.